2006
DOI: 10.1002/tie.20101
|View full text |Cite
|
Sign up to set email alerts
|

Patent protection and foreign direct investment

Abstract: The importance of development and use of products embodying intellectual property rights has increased dramatically. The growing share of knowledge‐intensive products in worldwide trade, together with the increase in international technological competition, has magnified the importance of patents and other forms of intellectual property. The objective of this study is to examine the effect of patent protection on inward foreign direct investment (FDI). It also examines the relative importance of other variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
5
21
1
Order By: Relevance
“…In addition, foreign investors, in all industries, tend to set up distribution facilities rather than engaging in local production in a country with weak IPR protection [60]. Four studies confirmed that MNEs prefer investing in the regions that have better intellectual property rights protection [61-63]. For example, a one point increase in IPR index would boost FDI by $1.5 billion [64].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, foreign investors, in all industries, tend to set up distribution facilities rather than engaging in local production in a country with weak IPR protection [60]. Four studies confirmed that MNEs prefer investing in the regions that have better intellectual property rights protection [61-63]. For example, a one point increase in IPR index would boost FDI by $1.5 billion [64].…”
Section: Resultsmentioning
confidence: 99%
“…Seyoum () tests the impact of IPRs on FDI across a random sample of 63 (developed and developing) countries for two time periods, 1990 and 1995. His model includes many theory‐based variables as controls.…”
Section: Empirical Evidence On the Impact Of Ipr Protection On Fdimentioning
confidence: 99%
“…The impact of IPR protection is positive and significant in both 1990 and 1995 (results partially contradicting those of Seyoum, ). Seyoum's () study would have benefited from the use of more granular data to establish if there is a difference in the importance of IPRs by sector or technological intensity, or to detect the impact of IPR protection on FDI driven by contrasting motives (e.g. market‐ or asset‐seeking).…”
Section: Empirical Evidence On the Impact Of Ipr Protection On Fdimentioning
confidence: 99%
“…This is because strong IPR encourages holders of intellectual property to trade and invest, as adequate protection of IPR assure foreign investors that their technology will not be leaked to competitors. As a result, the smaller risk of imitation leads to a larger net demand for protected products (Mansfield, 1994;Seyoum, 2006). A country that enhances its IPR regime may attract additional knowledge intensive products, which will otherwise be unavailable on the local market or it may attract FDI; in either case, international technology transfer is likely to flow (Lippoldt, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such advantages make it profitable to locate a business abroad. This means that FDI is not only "pushed" by firm specific advantages of the investor but may also be "pulled" to locations that are important sites of innovation activities (Seyoum, 2006). Further, it might be more profitable for the firm to internalize production rather than license or export goods on the open market.…”
Section: Literature Reviewmentioning
confidence: 99%